WORD OF MOUTH AND PERSONAL SELLING TO INCREASE PURCHASE DECISION OF READYMIX CONCRETE PRODUCTS THROUGH COMPETITIVE ADVANTAGE AND CORPORATE TRUST : Universitas 17 Agustus 1945 Surabaya - Dwi Anugrah Putra, Rakmat; Halik, Abdul; Budiarti, Endah (Jurnal Ekonomi Bisnis Manajemen dan Akuntansi (JEBISMA), 2024)
This research integrates two marketing approaches that are often considered separately, word of mouth (WOM) and personal selling, to explore their influence on purchase decision in the context of concrete products. This study offers new insights into the synergy of these two strategies in influencing purchase decisions by considering the role of corporate trust and competitive advantage as mediator variables. Corporate trust serves as a link between the influence of WOM and personal selling on purchase decision, while competitive advantage allows companies to offer products that are superior to their competitors. This research uses a quantitative approach with causal explanatory. The population in this study were customers of PT Varia Usaha Beton Gresik branch who made cash purchases of ready-mixed concrete products in July-September 2024. The sample used in this study was 103 respondents. This research uses purposive sampling method. The results showed that word of mouth has a significant effect on competitive advantage, personal selling has a significant effect on competitive advantage, word of mouth has a significant effect on corporate trust, personal selling has a significant effect on corporate trust, word of mouth has a significant effect on purchase decision, personal selling has an insignificant effect on purchase decision, competitive advantage has an insignificant effect on purchase decision, corporate trust has an insignificant effect on purchase decision of readymix concrete products at PT. Varia Usaha Beton in Gresik.